A dual-band diamond-shaped antenna for RFID application - Sabran, Mursyidul Idzham (Institute of Electrical and Electronics Engineers, 2011)
A novel dual-band single-layer substrate and diamond-shaped antenna is presented. The proposed antenna operates in dual-band frequency at UHF band (from 902 to 920 MHz) and ISM band (from 2.4 to 2.5 GHz), which is suitable for RFID application. Antenna frequencies were controlled by the shape and size of the radiating element. The proposed prototype antenna also has acceptable performances in terms of gain, efficiency, and directional radiation pattern. The antenna's gain and efficiency are 7.8 dBi and 87 %, respectively, at the lower frequency band, while the corresponding values are 9.4 dBi and 94 % at the higher band. When compared to the simulated results, the measurements show good agreement in terms of return loss and radiation pattern.